Associations between internet addiction and school engagement among Turkish college students: mediating role of psychological distress - Öztekin, Gülçin Güler (Frontiers in Psychology, 2024)
Introduction Internet addiction has become a subject of growing concern with adverse consequences. This study aimed to investigate the mediating effect of psychological distress in the relationship between internet addiction and school engagement. Methods Data were obtained from 732 Turkish college students (M = 20.98, SD = 2.58). The data were collected through Young’s Internet Addiction Test, Depression, Stress and Anxiety Scale (DASS21)-Short Form, and University Student Engagement Inventory. Mediation analysis was performed to investigate the mediating effects of depression, anxiety, and stress in the association between internet addiction and school engagement. Results The results of the study showed that internet addiction was positively associated with psychological distress and negatively associated with school engagement, whereas psychological distress had a negative relationship with school engagement. This study also found that depression, anxiety, and stress acted as mediators in the relationship between internet addiction and behavioral engagement, emotional engagement, and cognitive engagement. Conclusion This study has provided evidence that young adults with tendency of internet addiction may experience school engagement problems as well as psychological problems. Our findings underscore the need for special educational intervention programs aimed at encouraging college youth to limit their internet use for their future due to its negative consequences and raising awareness in this vulnerable group and their families.